Can the Spinal Cord Learn and Remember? - Pierre A. Guertin (The Scientific World Journal)
Learning and memory traditionally have been associated with cellular processes occurring in a specialized region of the brain called the hippocampus. However, recent data have provided strong evidence to suggest that comparable processes are also expressed in the spinal cord. Experiments performed mainly in spinal cord–transected animals have reported that, indeed, spinal-mediated functions, such as the stretch or flexion reflex, pain signaling, micturition, or locomotion, may undergo plasticity changes associated with partial functional recovery that occur spontaneously or conditionally. Many of the underlying cellular mechanisms strikingly resemble those found in the hippocampus. This mini-review reports, mainly, animal data that support the idea that other areas of the central nervous system, such as the spinal cord, can also learn and remember.